New SEPIC Derived Semi-Bridgeless PFC Converter for Battery Charging Application - Manish Kumar Dwivedi; R. Jayapragash (IEEE Access)
This paper introduces an AC-DC semi-bridgeless dual-switch SEPIC converter, specifically designed for battery charging applications. It focuses on improving power factor (PF) by substantially reducing total harmonic distortion (THD) in the AC input current through a modified converter structure. Additionally, the converter achieves significant reductions in the sizes of its inductors as it operates in discontinuous conduction mode (DCM) to achieve the low current THD. This converter topology employs two power switches to realize the power factor correction (PFC). Primary novelty of the proposed converter lies in designing and selecting a circuit structure which ensures low THD and unity power factor by the energy balance principle of inductors and capacitors. Additionally, the incorporation blocking diodes in the proposed converter effectively eliminates circulating current through input inductor which in turn makes the converter more efficient. This novel circuit structure also eliminates the requirement of additional closed loop control algorithm for PFC. To validate the proposed concept, a prototype converter of 100W/53V is developed and tested. This converter yields a current THD of 2.1%, unity PF and efficiency of 92.4% at rated condition during hardware testing. The paper also conducts a comparative analysis with similar other converters to assess the performance of the proposed solution thoroughly. This comprehensive study underscores the effectiveness of the new converter for PFC and reducing input current THD for battery charging applications.